2014
DOI: 10.1515/probus-2013-0003
|View full text |Cite
|
Sign up to set email alerts
|

Initial peaks and final falls in the intonation of Manchego Spanish wh-questions

Abstract: This paper investigates the phonetics and phonology of initial peaks and final falls in wh-questions produced by speakers of the variety of Spanish spoken in the Castile-La Mancha (Manchego) region of Spain. The acoustic analysis is based on speech data for nine speakers, and the goal is to identify how utterance-initial and utterance-final F 0 gestures relate to broader issues in intonational phonology and the prosodic signaling of wh-questions. The findings for left periphery constituents provide evidence fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…This work presents the main intonation patterns of this dialect together with phonetic variation contributing to the literature that documents intonation variation in Spanish dialects (e.g., Prieto andRoseano 2009-2013;Henriksen 2014;Henriksen and García-Amaya 2012) as well as an enhancement of the dialectological mapping of Argentina. The present work also allowed for an interlectal comparison between the intonational patterns of the Tucumán Spanish variety and the Buenos Aires Spanish variety regarding a number of pragmatic conditions, a comparison that yielded interesting results, thus confirming previous impressionistic analysis.…”
Section: Resultsmentioning
confidence: 95%
“…This work presents the main intonation patterns of this dialect together with phonetic variation contributing to the literature that documents intonation variation in Spanish dialects (e.g., Prieto andRoseano 2009-2013;Henriksen 2014;Henriksen and García-Amaya 2012) as well as an enhancement of the dialectological mapping of Argentina. The present work also allowed for an interlectal comparison between the intonational patterns of the Tucumán Spanish variety and the Buenos Aires Spanish variety regarding a number of pragmatic conditions, a comparison that yielded interesting results, thus confirming previous impressionistic analysis.…”
Section: Resultsmentioning
confidence: 95%
“…Most experimental work has focused on F0 movements in phrase-final position, due to their pragmatic, stylistic and regional variation (Estebas-Vilaplana and Prieto, 2010;Henriksen, 2009Henriksen, , 2013Henriksen, , 2014López-Bobo and Cuevas-Alonso, 2010;Prieto, 2004;Sosa, 1999). Navarro Tomás (1948), in his treatise on Spanish intonational structure, distinguishes 3 melodic contours used to signal wh-question intent, displayed in figure 2: a default falling contour (2a), a pragmatically motivated 'polite' contour characterized by a final rise (2b) and a circumflex contour characterized by a final rise-fall that communicates amazement or surprise (2c).…”
Section: Spanish Wh-question Intonationmentioning
confidence: 99%
“…Whereas Sosa (1999, p. 148) proposed the H* + H label to describe the initial rising accent in whquestions, Prieto considered the possibility of a phonologically distinct upstepped ¡H accent on the wh-word, but left this open for further analysis. At the time of writing, Henriksen (2014) is the most recent analysis of Peninsular Spanish wh-question intonation, framing the acoustic findings within the AM framework. The speakers in Henriksen's paper produced wh-questions with a rise at the left periphery followed by a fall (H + L*) or rise-fall (L + ¡H*) on the nuclear syllable, and an L% boundary tone ( fig.…”
Section: Spanish Wh-question Intonationmentioning
confidence: 99%
“…These configurations occur in most varieties of Peninsular Spanish, documented for northern, central, and southern varieties (Prieto 2004;Henriksen 2009;Estebas-Vilaplana and Prieto 2010;López-Bobo and Cuevas-Alonso 2010;Henriksen and García-Amaya 2012;Henriksen 2013). The phonetic properties of the H þ L* and L þ ¡H* accents were examined in Henriksen (2014), where it was shown that the leading tones aligned within the last portion of the prestressed syllable and the starred tones aligned within the second half of the nuclear syllable. However, a recognized caveat was that only open syllables were included in the database of test sentences in Henriksen (2014).…”
mentioning
confidence: 99%
“…The phonetic properties of the H þ L* and L þ ¡H* accents were examined in Henriksen (2014), where it was shown that the leading tones aligned within the last portion of the prestressed syllable and the starred tones aligned within the second half of the nuclear syllable. However, a recognized caveat was that only open syllables were included in the database of test sentences in Henriksen (2014). It remains to be seen whether the alignment of starred tones remains synchronous with the syllable edge when the nuclear rhyme incorporates a coda consonant.…”
mentioning
confidence: 99%